A Comparative Analysis of K-Means Clustering Algorithm and Expectation-Maximation (EM) for Classification of Grain Rice - Septiana, Lina; Djohan, Nani (Teknik dan Ilmu Komputer, 2015)
AbstrakÃÂ Penelitian ini mengamati perbandingan klasifikasi butir beras menggunakan algoritma K-means clustering dan Expectation-Maximation. Jenis beras yang digunakan dalam penelitian ini adalah butir beras Taiwan dan butir beras Thailand. Hal ini dilakukan menggunakan pengenalan pola unsupervised dengan mengidentifikasi panjang dan lebar dari kedua jenis butir beras tersebut, yaitu beras Taiwan CNS grade 1 dan beras Thailand Thai Hom Mali grade A. Hasil analisis menunjukkan kedua metode tersebut memberikan hasil yang hampir sama dalam pengelompokan kedua jenis beras tersebut.ÃÂ Kata kunci: pengelompokan K-means, pengenalan pola unsupervisedÃÂ ÃÂ AbstractÃÂ This study observed the comparison of rice grain classification using K-means clustering algorithm and Expectation-Maximation Algorithm. This research uses Taiwanese rice grain and Thai rice grain. The study was performed using the unsupervised pattern recognition by identifying the length and width of two different rice grains, which are CNS Taiwan rice Grade 1 (Taiwanese rice) and Thai Hom Mali Rice Grade A (Thai rice). The analysis result shows these two methods have a similar result in clustering the two kinds of rice grains.ÃÂ Key words: k-means clustering, unsupervised pattern recognition.